2020
DOI: 10.1080/23748834.2020.1767014
|View full text |Cite
|
Sign up to set email alerts
|

Researching on sanitation behaviour and practices in low- income settlements: the need for sensitivity, skill, and creativity

Abstract: Due to inadequate sanitation services, residents of low-income settlements practice open defecation or use other methods for faecal waste disposal. Such residents may not easily disclose their sanitation practices or behaviour since it requires them to disclose information that may be considered personal. Research on sanitation practices in these settings requires skill, creativity, and appropriate data collection methods. This article draws insights from research conducted in low-income settlements of Kisumu … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 52 publications
1
2
0
Order By: Relevance
“…It is in contrast with other studies which found pit latrines to be the dominant shared sanitation technology [ 37 , 45 ]. In Kenya, the distribution of shared sanitation technologies reflects the findings from earlier studies [ 42 , 46 ]. Almost all (96%) of the sanitation facilities in both countries were within the compound premises, while the rest were within users’ reach though outside the compound.…”
Section: Resultssupporting
confidence: 75%
“…It is in contrast with other studies which found pit latrines to be the dominant shared sanitation technology [ 37 , 45 ]. In Kenya, the distribution of shared sanitation technologies reflects the findings from earlier studies [ 42 , 46 ]. Almost all (96%) of the sanitation facilities in both countries were within the compound premises, while the rest were within users’ reach though outside the compound.…”
Section: Resultssupporting
confidence: 75%
“…Meanwhile, research on sanitation practices requires skills, creativity, and appropriate data collection methods (Simiyu, 2022). In the food industry, sanitation is creating and maintaining hygienic and healthy conditions.…”
Section: Results and Discussion Hygienic And Sanitationmentioning
confidence: 99%
“…Some of these things are crucial to avoid the transmission of covid-19 [4]. The attitudes and behaviors people choose can affect their hygiene behavior, in addition to cultural, societal, and family conventions, their level of education, their socioeconomic situation, and other factors [5] changes might result from physical problems. In addition, psychological illnesses may develop due to these conditions since they may lessen the appeal of physical beauty and emotional responses.…”
Section: Introductionmentioning
confidence: 99%